The “Slightly Smiling Face” Emoji in WeChat: A Conversation Analytic Investigation - Zhuolei Li (Studies in Applied Linguistics & TESOL, 2025)
This study investigates the interactional functions of the “Slightly Smiling Face” (SSF) emoji in Chinese WeChat conversations through the lens of Conversation Analysis (CA). Drawing on 50 naturally occurring chat excerpts involving 12 participants across various relationship types, the study identifies three core uses of the SSF emoji: (1) signaling sequence-closing, (2) mitigating dispreferred actions, and (3) conveying disaffiliation without explicit disagreement. These functions parallel some of the roles traditionally fulfilled by nonverbal cues in face-to-face interactions, such as smiles or laughter tokens, revealing how digital communication retools physical gestures through symbolic surrogates. While prior research on emoji use often relies on statistical or multimodal analysis, this paper offers a context-sensitive examination that underscores how a single emoji can accomplish varied pragmatic work depending on sequential positioning and interactional context. By centering on a culturally embedded and pragmatically ambiguous emoji, the study contributes to the understanding of digital CA and broadens the scope of emoji research beyond Western platforms.